The effect of type, duration and intensity of exercise on inflammatory markers CRP, IL-6 and IL-18 in metabolic syndrome patients : a systematic review - Srijit Dass; Isa Naina-Mohamed; S Zulfarina Mohamed; Hazwan Hazrin Salim; Azwani Zawawi; Tarrsini Thevaraj; Ku Nurmahirah Ku-Ahmad-Nasir; Kheng, Dennis Zhou; Teoh, Seong Lin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Metabolic syndrome (MetS) has become a major clinical challenge worldwide due to rise of urbanisation, surplus energy intake, increasing obesity and sedentary lifestyle. C-reactive protein (CRP), interleukin-6 (IL-6) and interleukin-18 (IL-18) are associated with MetS. We performed a systematic review to investigate the effects of exercise on these markers in MetS patients and therefore to determine the best exercise regime for them. We searched Medline (Pubmed and Ovid), Scopus and CINAHL databases. The searches were standardized by using the same search strategy which included the terms such as ‘metabolic syndrome’, ‘CRP’, ‘IL-6’, ‘IL-18’ and ‘exercise’. Only clinical human studies published from Jan 2007 to May 2018 were included. A total of 11 clinical trials (466 participants) were selected. Majority of the studies were randomized controlled studies (90.9%). All studies showed a decrease in serum levels of the biomarkers. However, not all were statistically significant. The main type of exercise in most of the studies was aerobic. Aerobic-resistance exercise was more effective rather than aerobic alone, but aerobic exercise was the only effective as a sole intervention. Aerobic exercise showed promising role as the main lifestyle intervention in MetS. It is concluded that patients with MetS should have combined aerobic-resistance exercise.